(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
In this editorial, the proposal that mobilized the editors is presented: various discussions about the practice of Nelson Rodrigues’ work on stage. The different texts that make up the dossier discuss staging of Rodriguean plays, chronicles and novels and are briefly commented on in this opening text of the dossier.